Algal Biodiesel in Lithuania: From Promise to Reality. (2016) - Felneris, Mantas; Raslavičius, Laurencas
Abstract: The search for alternative fuel sources of organic origin, their adaptation and promotion emerged as one of the key focus areas worldwide, which could bring positive effect on lowering down the fossil fuel prices and solving the environmental problems. Algal biodiesel intended for use in the vehicles is among the solutions for the transport sector. In this article, we made an overview of biodiesel investigation in Lithuania over 11 years. Algae are the third generation biofuel form with high production perspective. This microorganism can be found almost everywhere even in Arctic. Algae can be counted as 55 000 species organism with great number of growth and quantities of biomass per unit. Possibilities and challenges of biodiesel from algae in Lithuania have been analysed. Application and compatibility of algae biodiesel in internal combustion engine has been investigated. Many advantages of biodiesel have been presented as well as some disadvantages were found.